2019
DOI: 10.1037/xhp0000641
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of expended effort and intent does not affect estimates of slant or distance.

Abstract: It is well known that people overestimate the orientation of both geographical and man-made sloped surfaces by between 5°-20°. More recently, work has shown that when people are encumbered by wearing a heavy backpack they overestimate hills and distances even more than a group not wearing heavy backpacks; however, the backpack manipulation has since been shown to be a demand effect-that is, being encumbered does not affect perception-it only biases those people influenced by it to give estimates the experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“… Taylor, Witt & Sugovic (2011) found that traceurs/parkour athletes ( i.e ., higher fitness/sport-specific training) estimated vertical wall height as significantly lower than untrained controls for a 1.94 m wall but not for higher walls (2.29 m, 3.45 m). Effect sizes were unable to be calculated for two other studies, but one found a non-significant relationship between waist-to-hip ratio and distance perception ( Cole, Balcetis & Zhang, 2013 ), and one found no relationship between self-rated fitness and a distance on hill measure ( Shaffer, Greer & Schaffer, 2019 ).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“… Taylor, Witt & Sugovic (2011) found that traceurs/parkour athletes ( i.e ., higher fitness/sport-specific training) estimated vertical wall height as significantly lower than untrained controls for a 1.94 m wall but not for higher walls (2.29 m, 3.45 m). Effect sizes were unable to be calculated for two other studies, but one found a non-significant relationship between waist-to-hip ratio and distance perception ( Cole, Balcetis & Zhang, 2013 ), and one found no relationship between self-rated fitness and a distance on hill measure ( Shaffer, Greer & Schaffer, 2019 ).…”
Section: Resultsmentioning
confidence: 95%
“…All experiments had high risk of bias ( Table 2 ). No experiments used random sampling and only 4% ( n = 3/68) performed a priori sample size calculations ( Scandola et al, 2019 ; Shaffer, Greer & Schaffer, 2019 ). Four experiments ( Dean et al, 2016 ; Durgin et al, 2012 ; Shaffer et al, 2013 ; Taylor-Covill & Eves, 2013 ) had low risk of bias for the spatial perception measure ( i.e ., reliability established by previous research).…”
Section: Resultsmentioning
confidence: 99%